Jacques Viger: une biographie. Suivi des lettres de Jacques et Marguerite, 1808-1813 - Beaudoin, Léo; Blanchet, Renée (Études québécoises, 2009)
Keywords: Lacorne (famille); Maires; Milice; Société historique de Montréal; Viger, Jacques

Le discours de guerre tenu aux enfants montréalais au sujet de la Première Guerre mondiale entre 1914 et 1918 - Cardinal, Sophie (Université de Montréal, 2009)
Keywords: Enfants; Guerre; Montreal Witness; Patrie (La); Presse (La)

La gouvernance militaire en Nouvelle-France - Chartrand, René (Bulletin d'histoire politique, 2009)
Keywords: Armée

Les Fusiliers Mont-Royal au débarquement de Dieppe. Doctrine et entraînement au Canada et en Angleterre 1939-1942 - D'Amours, Caroline (Université Laval, 2009)
Keywords: Armée; Fusiliers Mont-Royal; Guerre

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey, Daniel; Émeutes

1940-1948, les éditeurs québécois et l'effort de guerre - Michon, Jacques (Presses de l'Université Laval et Direction de la programmation culturelle de la BAnQ, 2009)
Keywords: Guerre; Édition

After Ryswick: The Five Nations Iroquois in French Diplomacy - Miquelon, Dave B. (Native Studies Review, 2009)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

Le fort et les poudrières du complexe militaire de l'île Sainte-Hélène - Royer, Martin (Université Laval, 2009)
Keywords: Armes; Fortifications; Forts; Île Sainte-Hélène

La guerre vue de Westmount - Willis, John (Cap-aux-Diamants, 2009)
Keywords: Guerre; Westmount

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet, Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard, Valentin; Journalistes; Librairie; Mesplet, Fleury

Divided by the Ballot Box: The Montreal Council of Women and the 1917 Election - Brookfield, Tarah (Canadian Historical Review, 2008)
Keywords: Femmes; Féminisme; Montreal Local Council of Women; Élections

The October Crisis of 1970: Human Rights Abuses under the War Measures Act - Clément, Dominique (Journal of Canadian Studies / Revue d'études canadiennes, 2008)
Keywords: Crise d'octobre; Front de Libération du Québec; Trudeau, Pierre Elliott

Vivre comme frères: Native-French Alliances in the St Lawrence Valley, 1535-1667 - Cook, Peter (Université McGill, 2008)
Keywords: Autochtones; Français

Le Roi, l'Église et la guerre: la prédication à Montréal au moment de la conquête (1750-1766) - Décary, Simon (Université de Montréal, 2008)
Keywords: Communautés religieuses; Sulpiciens

Les Pointeliers en guerre - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Armée; Guerre; Milice; Pointe-aux-Trembles; Quartiers

Onontio, le médiateur: la gestion des conflits amérindiens en Nouvelle-France, 1603-1717 - Gohier, Maxime (Septentrion, 2008)
Keywords: Autochtones; Français

La stratégie lors de l'affrontement anglo-américain au Canada (1775-1776). Objets politiques et objectifs militaires - Nadeau, Charles André (Université Laval, 2008)
Keywords: Américains; Armée; Britanniques

Philippe de Rigaud de Vaudreuil, gouverneur. De mousquetaire à vice-roi - Payant, Robert (Célébrités / Collection biographique, 2008)
Keywords: Gouverneurs; Rigaud de Vaudreuil, Philippe de

Les relations franco-québécoises pendant la Grande Guerre - Pépin, Carl (Université Laval, 2008)
Keywords: Français; Guerre

Victor Brodeur. Officier de la marine canadienne, 1909-1946 - Rawling, Bill (Histoire militaire, 2008)
Keywords: Armée

Iberville et les historiens. Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Histoire; Historiens; Le Moyne d'Iberville et d'Ardillières, Pierre

The Club and the Two World Wars / Le Club et les deux guerres mondiales - Claxton, John B. (University Club of Montreal, 1907-2007 / Le Club Universitaire de Montréal, 1907-2007, 2007)
Keywords: Clubs; Guerre; Poésie; University Club; Université McGill

Sur le front intérieur. Les ménagères québécoises de la seconde guerre mondiale: rationnement et récupération - St-Onge, Mélissa (Université de Montréal, 2007)
Keywords: Femmes; Guerre

Le corps amérindien dans les relations de voyage en Nouvelle-France au XVIIIe siècle - Chaffray, Stéphanie (Université Laval et Université Paris IV-Sorbonne, 2006)
Keywords: Autochtones; Français

Les soldats français à Montréal au XVIIIe siècle: activités et intégration sociale des soldats vues à travers les sources judiciaires - Charland, Stéphanie (Université de Montréal, 2006)
Keywords: Armée; Français

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (Studies in Canadian Military History Series, 2006)
Keywords: Guerre; Quartiers; Verdun

A Man's a Man because of That: The Scots in the Canadian Military Experience - Klepak, H. P. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Armée; Écossais

"Tant vaut la sève, tant vaut l’érable." Les corps de cadets collégiaux québécoise (1879-1914) - Normand, France (Université de Montréal, 2006)
Keywords: Collège Sainte-Marie

Facteurs de motivation des cadets et des cadettes au sein des unités francophones de Montréal - Bronsard, Martin (Université du Québec à Trois-Rivières, 2005)
Keywords: Francophones

La radicalisation et la militarisation des Loyaux et des Patriotes à Montréal en 1837 - Cyr, Bruno (Université de Montréal, 2005)
Keywords: Loyalistes; Rébellions

"Cy devant soldat - après habitant": The Settling of the Carignan-Salières Regiment in New France - Gagné, Peter (Université Laval, 2005)
Keywords: Armée

WILSON, ERASTUS WILLIAM - Gagnon, Jean-Pierre (Dictionnaire biographique du Canada, 2005)

FORBES, ALEXANDER MACKENZIE TORRANCE - Hanaway, Joseph (Dictionnaire biographique du Canada, 2005)

RODDICK, sir THOMAS GEORGE - Hanaway, Joseph (Dictionnaire biographique du Canada, 2005)

SCOTT, HENRI-THOMAS - Janson, Gilles (Dictionnaire biographique du Canada, 2005)

La milice du district de Montréal, 1787-1829: essai d'histoire socio-militaire - Lépine, Luc (Université du Québec à Montréal, 2005)
Keywords: Milice

MEREDITH, sir HENRY VINCENT - McDowall, Duncan (Dictionnaire biographique du Canada, 2005)

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Keywords: Guerre; Lachine; Émeutes

ASSELIN, OLIVAR - Pelletier-Baillargeon, Hélène (Dictionnaire biographique du Canada, 2005)

VALLÉE, CHARLES-AMÉDÉE - Tremblay, Marie J. (Dictionnaire biographique du Canada, 2005)

Chant et mission en Nouvelle-France, espace et rencontre des cultures - Dubois, Paul-André (Université Laval, 2004)
Keywords: Autochtones; Chanson; Missions; Musique

Onontio, le médiateur: la gestion des conflits amérindiens en Nouvelle-France, 1603-1717 - Gohier, Maxime (Université du Québec à Montréal, 2004)
Keywords: Autochtones; Français

Moe de Montréal: 1917-1942 - Willis, John (Cap-aux-Diamants, 2004)
Keywords: Guerre

LARICHELIÈRE, JOSEPH-ÉMILE-PAUL - Cooke, Owen A.; Ashmore, Mark (Dictionnaire biographique du Canada, 2003)

James McGill of Montreal : citizen of the Atlantic world - Cooper, John Irwin (Borealis Press, 2003)
Keywords: Autochtones; Fourrure; Marchands; McGill, James

GASS, LELIA CLARE - Mann, Susan (Dictionnaire biographique du Canada, 2003)

Un fort Gentilly à la Grande Anse? À la recherche d'une réponse - Pasquin, Michel (Héritage Dorval, 2003)
Keywords: Cartes et plans; Dorval; Forts

Portrait d'un ARGOULET. Pierre Raguideau et la recrue de 1653 à Ville-Marie - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2002)
Keywords: Autochtones; Engagés; Guerre; Iroquois; Milice

De la Grande Paix de 1701 à la Grande Guerre de Montréal de 1990 - Trudel, Pierre (Bulletin d'histoire politique, 2002)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre

The Last French and Indian War: an Inquiry Into a Safe-Conduct Issued in 1760 that Acquired the Value of a Treaty in 1990 - Vaugeois, Denis (McGill-Queen's University Press et Septentrion, 2002)
Keywords: Autochtones; Français

Le tricentenaire de la Grande Paix de Montréal. Août 1701 - Beaudoin, Léo (Histoire Québec, 2001)
Keywords: Autochtones; Callière, Louis-Hector de; Français; Gouverneurs; Grande Paix de Montréal; Guerre; Iroquois

2001: tricentenaire de la Grande Paix de Montréal - Beaudoin, Léo (Montréal en tête, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Le tricentenaire de la Grande Paix de Montréal. Louis-Hector de Callière (1646-1703), artisan de la Grande Paix - Beaudoin, Léo (Montréal en tête, 2001)
Keywords: Callière, Louis-Hector de; Gouverneurs; Grande Paix de Montréal

Le tricentenaire de la Grande Paix de Montréal. Montréal, juillet-août 1701 - Beaudoin, Léo (Montréal en tête, 2001)
Keywords: Autochtones; Callière, Louis-Hector de; Fortifications; Fourrure; Gouverneurs; Grande Paix de Montréal; Guerre

La Grande Paix: chronique d'une saga diplomatique - Beaulieu, Alain; Viau, Roland (Libre Expression et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

The Great Peace: Chronicle of a Diplomatic Saga - Beaulieu, Alain; Viau, Roland (Libre Expression, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Les origines de la Fédération des Sept Feux - Delâge, Denis; Sawaya, Jean-Pierre (Recherches amérindiennes au Québec, 2001)
Keywords: Autochtones

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Montréal, 1701: planter l'arbre de paix - Havard, Gilles (Signes des Amériques, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Montréal, 1701: Planting the Tree of Peace - Havard, Gilles (Signes des Amériques, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

The Great Peace of Montreal of 1701: French-Native Diplomacy in the Seventeenth Century - Havard, Gilles (McGill-Queen's University Press, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Les lieux de la paix de 1701, et autres considérations sur les campements amérindiens à Montréal - Johnson, Laurence (Recherches amérindiennes au Québec, 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal

Louis-Hector de Callière: homme de guerre, homme de paix - Morazain, Jeanne; Cloutier, Ginette; Lelievre, Francine (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2001)
Keywords: Callière, Louis-Hector de; Gouverneurs

Louis-Hector de Callière: Man of War, Man of Peace - Morazain, Jeanne; Cloutier, Ginette; Lelievre, Francine (Pointe-à-Callière, Cité d'archéologie et d'histoire de Montréal, 2001)
Keywords: Callière, Louis-Hector de; Gouverneurs

Olivar Asselin et son temps. Tome 2: Le volontaire - Pelletier-Baillargeon, Hélène (Fides, 2001)
Keywords: Asselin, Olivar; Journalistes; Écrivains

Mobilizing Canada: the National Resources Mobilization Act, the Department of National Defence, and Compulsory Military Service in Canada - Byers, Daniel Thomas (Université McGill, 2000)
Keywords: Conscription; Guerre

Montréal, le mouvement ouvrier et la Première Guerre mondiale - Dansereau, Bernard (Bulletin d'histoire politique, 2000)
Keywords: Guerre

L'organisation de la milice de la région montréalaise de 1792 à 1837: de la paroisse au comté - Dion, Dominique; Legault, Roch (Bulletin d'histoire politique, 2000)
Keywords: Milice

La Deuxième Guerre mondiale dans la mémoire collective canadienne-française / québécoise à travers le «mythe» de Dieppe 1942-1995 - Richard, Béatrice (Université du Québec à Montréal, 2000)
Keywords: Commémoration; Guerre